Constructing Na‐Ion Cathodes via Alkali‐Site Substitution. (27th February 2020) - Zhao, Chenglong; Yao, Zhenpeng; Zhou, Dong; Jiang, Liwei; Wang, Jianlin; Murzin, Vadim; Lu, Yaxiang; Bai, Xuedong; Aspuru‐Guzik, Alán; Chen, Liquan; Hu, Yong‐Sheng
Abstract: Na‐ion batteries have experienced rapid development over the past decade and received significant attention from the academic and industrial communities. Although a large amount of effort has been made on material innovations, accessible design strategies on peculiar structural chemistry remain elusive. An approach to in situ construction of new Na‐based cathode materials by substitution in alkali sites is proposed to realize long‐term cycling stability and high‐energy density in low‐cost Na‐ion cathodes. A new compound, [K0.444(1) Na1.414(1) ][Mn3/4 Fe5/4 ](CN)6, is obtained through a rational control of K + content from electrochemical reaction. Results demonstrate that the remaining K + (≈0.444 mol per unit) in the host matrix can stabilize the intrinsic K‐based structure during reversible Na + extraction/insertion process without the structural evolution to the Na‐based structure after cycles. Thereby, the as‐prepared cathode shows the remarkably enhanced structural stability with the capacity retention of >78% after 1800 cycles, and a higher average operation voltage of ≈3.65 V versus Na + /Na, directly contrasting the non‐alkali‐site‐substitution cathode materials. This provides new insights into alkali‐site‐substitution constructing advanced Na‐ion cathode materials. Abstract : An approach to in situ construct new Na‐based cathode materials is proposed to realize high‐energy density and long‐term cycling stability for low‐cost Na‐ion batteries. [K0.444(1) Na1.414(1) ][Mn3/4 Fe5/4 ](CN)6, as a proof‐of‐concept study, is obtained, and exhibits improved electrochemical properties, in particular ultra‐stable cycling capability.